Characterization of Feedback Neurons in the High-Level Visual Cortical Areas That Project Directly to the Primary Visual Cortex in the Cat - Pan, Huijun; Zhang, Shen; Pan, Deng; Ye, Zheng; Yu, Hao; Ding, Jian; Wang, Qin; Sun, Qingyan; Hua, Tianmiao (Frontiers in Neuroanatomy, 2021)
Previous studies indicate that top-down influence plays a critical role in visual information processing and perceptual detection. However, the substrate that carries top-down influence remains poorly understood. Using a combined technique of retrograde neuronal tracing and immunofluorescent double labeling, we characterized the distribution and cell type of feedback neurons in cat’s high-level visual cortical areas that send direct connections to the primary visual cortex (V1: area 17). Our results showed: 1) the high-level visual cortex of area 21a at the ventral stream and PMLS area at the dorsal stream have a similar proportion of feedback neurons backprojecting to the V1 area. 2) the distribution of feedback neurons in the higher order visual area 21a and PMLS was significantly denser than in the intermediate visual cortex of area 19 and 18. 3) feedback neurons in all observed high-level visual cortex were found in layer II-III, IV, V and VI, with a higher proportion in layer II-III, V and VI than in layer IV. 4) most feedback neurons were CaMKII-positive excitatory neurons, and few of them was identified as inhibitory GABAergic neurons. These results may argue against the segregation of ventral and dorsal streams during visual information processing, and support ‘reverse hierarchy theory’ or interactive model proposing that recurrent connections between V1 and higher order visual areas constitute the functional circuits that mediate visual perception.In addition, the corticocortical feedback neurons from high-level visual cortical areas to the V1 area are mostly excitatory in nature.